2020
DOI: 10.1080/00051144.2020.1816388
|View full text |Cite
|
Sign up to set email alerts
|

FPGA implementation of hardware architecture with AES encryptor using sub-pipelined S-box techniques for compact applications

Abstract: Advanced Encryption Standard (AES) is a thriving cryptographic algorithm that can be utilized to guarantee security in electronic information. It remains to uphold to be resistive from most of the attacks. In this work, AES-128 encryption iterative architecture is designed to achieve minimum area and less hardware utilization. Reduced area is attained by introducing a renovated S-box structure into the AES algorithm. Furthermore, hardware utilization is minimized by incorporating the Vedic multiplier in the Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…A combined-block strategy employing Key Expansion design for improving the throughput and for minimizing the power usage was introduced by Kalaiselvi [22]. In numerous additional scientific studies [23][24][25][26][27], various degrees of pipelined architectures were suggested. Granado et al [28] created a high-speed AES formula execution for Wi-FI Protected Access 2 (WPA2) systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A combined-block strategy employing Key Expansion design for improving the throughput and for minimizing the power usage was introduced by Kalaiselvi [22]. In numerous additional scientific studies [23][24][25][26][27], various degrees of pipelined architectures were suggested. Granado et al [28] created a high-speed AES formula execution for Wi-FI Protected Access 2 (WPA2) systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Arul et al [44] developed the Iterative Structure of the AES (ISAES) for lessening the hardware resources. The architecture of renovated S-box was used in the AES to minimize the area.…”
Section: Introductionmentioning
confidence: 99%
“…The hardware resources also increased because of AES design using non-pipelined stages [41]. Due to the high delay, the operating frequency is decreased in the AES architecture [44]. The area of the overall AES is increased because of the replication of linear function and independent operation [45].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, symmetric cryptography is less complex and executes faster than asymmetric cryptography, and so it has been accepted as an industry-standard cryptographic algorithm and is being widely used to secure sensitive, secret, or classified information in government, healthcare, banking, and other industries. Previously researchers proposed plenty of symmetric cryptographic algorithms [ 7 11 ]. Advanced Encryption Standard (AES) is one of the most secured and chosen US NIST of USA Govt for its military among the multiple cryptographic algorithms.…”
Section: Introductionmentioning
confidence: 99%